1992
DOI: 10.1038/ki.1992.141
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous pancreas-kidney transplant versus kidney transplant alone in diabetic patients

Abstract: The decision for simultaneous pancreas-kidney (SPK) versus kidney transplant alone (KTA) in diabetic patients with renal failure depends on the potential risks and benefits for each procedure. The purpose of this study was to compare the morbidity, mortality, and renal allograft survival in diabetic patients who underwent SPK versus KTA, and to discern the added risks associated with pancreas transplantation. Between 7/1/86 and 9/30/90, 69 primary cadaver SPK and 59 primary cadaver KTA were performed in type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Several other comparisons of SPK and cadaveric renal transplantation in diabetic patients have been published. Cheung et al 27 from Minnesota showed that for patients younger than 45 years, there was no difference in 2-year patient or graft survival rates, but older patients receiving cadaveric kidneys alone fared significantly better than older SPK recipients. The Iowa group, who analyzed a cohort of patients younger than 45 years, showed no difference in long-term survival between cadaveric and SPK recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Several other comparisons of SPK and cadaveric renal transplantation in diabetic patients have been published. Cheung et al 27 from Minnesota showed that for patients younger than 45 years, there was no difference in 2-year patient or graft survival rates, but older patients receiving cadaveric kidneys alone fared significantly better than older SPK recipients. The Iowa group, who analyzed a cohort of patients younger than 45 years, showed no difference in long-term survival between cadaveric and SPK recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore believe that the late pancreas graft losses secondary to chronic rejection in AA most likely result from inadequate treatment of pancreas rejection episodes rather than from a failure of rejection surveillance. It is well known that rejection is not only more common in SPK, but also more likely to be steroid resistant and recurrent than in kidney transplant alone (43)(44)(45). Papadimitriou et al have shown while minimal and mild episodes of pancreas rejection have a good response to steroids, higher grades of rejection are more likely to be steroid resistant and require antibody therapy (46).…”
Section: Discussionmentioning
confidence: 99%
“…Infections are more common in kidney-pancreas transplant recipients compared to kidney transplantation alone (950,952,953). Simultaneous kidney-pancreas transplantation has been associated with a higher incidence of acute renal allograft rejection (954,955).…”
Section: Endocrinementioning
confidence: 99%